2022
DOI: 10.1002/hep.32318
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Homolog 2 contributes to liver oncogenesis by promoting unfolded protein response–dependent destabilization of tumor protein P53

Abstract: Backgroud and Aims: Abnormalities in the tumor protein P53 (p53) gene and overexpression of mouse double minute 2 homolog (MDM2), a negative regulator of p53, are commonly observed in cancers. p53 destabilization is regulated by endoplasmic reticulum (ER) stress and unfolded protein response (UPR) in cancer. However, the mechanisms remain enigmatic.Canopy homolog 2 (CNPY2) is a key UPR initiator that primarily involved in ER stress and is highly expressed in the liver, but its functional role in regulating liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Therefore, the quest for more effective ways to treat HCC is of great significance in improving the prognosis of HCC patients. Current studies have found that ERS is closely related to cell cycle regulation, activation and inhibition of proto-oncogenes and tumor suppressor genes, immune response, and changes in the tumor microenvironment during the occurrence and progression of HCC [106][107][108][109]. A recent study by Feng et al suggests that ERS in HCC cells can induce CNYP2, thereby activating three response pathways of UPR, inhibiting the expression of tumor suppressor gene p53 and shortening the cell cycle, ultimately promoting the occurrence of HCC [106].…”
Section: Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the quest for more effective ways to treat HCC is of great significance in improving the prognosis of HCC patients. Current studies have found that ERS is closely related to cell cycle regulation, activation and inhibition of proto-oncogenes and tumor suppressor genes, immune response, and changes in the tumor microenvironment during the occurrence and progression of HCC [106][107][108][109]. A recent study by Feng et al suggests that ERS in HCC cells can induce CNYP2, thereby activating three response pathways of UPR, inhibiting the expression of tumor suppressor gene p53 and shortening the cell cycle, ultimately promoting the occurrence of HCC [106].…”
Section: Liver Cancermentioning
confidence: 99%
“…Current studies have found that ERS is closely related to cell cycle regulation, activation and inhibition of proto-oncogenes and tumor suppressor genes, immune response, and changes in the tumor microenvironment during the occurrence and progression of HCC [106][107][108][109]. A recent study by Feng et al suggests that ERS in HCC cells can induce CNYP2, thereby activating three response pathways of UPR, inhibiting the expression of tumor suppressor gene p53 and shortening the cell cycle, ultimately promoting the occurrence of HCC [106]. Another study showed that ERS, when activated in liver cancer tissue, helps HCC cells to deliver exosome microRNA-23a-3p to macrophages, activate the PI3K-AKT pathway by inhibiting phosphatase and tensin homolog, and increase the expression of programmed death ligand 1.…”
Section: Liver Cancermentioning
confidence: 99%
“…This change indicated that FGF21 is an independent indicator of genetic hepatocarcinogenesis, but its expression is not a direct genetic marker of hepatoma cells per se 91 . Instead, a study showed that canopy homolog 2 promoted liver oncogenesis via destabilizing p53 and activating hepatic FGF21 expression 92 . Consistently, tumor suppressor miR-22 reduced hepatic FGFR1 by direct targeting and inhibited FGF21 expression by reducing its synthesis process 93 .…”
Section: Fgf21 Is a Promising Biomarker With Pleiotropic Activities I...mentioning
confidence: 99%
“…One of the adaptive response is the UPR. In tumors, upregulation of UPR significantly increased the proliferation rate through destabilization of antitumor protein [6] , promotion of oncogene transcription and angiogenesis [7] . In addition, UPR is also responsible for immune evasion via upregulating PD-L1 or MICA/B expression [8,9] , facilitating the production of pro-inflammatory and immunomodulatory cytokines, such as interleukin-8 (IL-8), CXC-chemokine ligand 1 (CXCL1) and so on [10] .…”
Section: Introductionmentioning
confidence: 99%